STRATEGI DALAM MEMBANGUN E-BUSINESS BAGI PELAKU UMKM MENUJU DIGITALISASI (BUILD E-BUSINESS FOR MSME ACTORS TOWARDS DIGITALIZATION) - A. A Gede Ajusta; Nurullah Nurullah Sururi Afif; Anantha Zakharia (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
This study aims to research methods used qualitative methods with reference to the Strategy to Build E-Business for MSME Actors Towards Digitalization. Data collection techniques through interviews with similar companies and Product Launching experts. The results of the analysis show that there are 4 things that must be done in building e-business for MSMEs including:1.Development of E-Business Architecture 2. Installation3. Selection of Development Options, 4.Applications that have been selected and implemented are expected to be well integrated with all existing applications.5. Operation/Maintenance.In building E-Business, it is not merely transferring conventional business into E-Business, but the most important thing is consistency in terms of updating information, technology, good systems, good management, fast service and response, and communication with customers or consumers. So that consumers become satisfied and continue to make repeat orders, it remains only for MSME entrepreneurs to continue to develop the market with promotions on various promotion platforms.